2021
DOI: 10.1002/gps.5603
|View full text |Cite
|
Sign up to set email alerts
|

Effects of virtual reality cognitive training in individuals with mild cognitive impairment: A systematic review and meta‐analysis

Abstract: Background: Virtual reality (VR) is used to improve specific health needs by combining multiple technologies; it is increasingly being used in the medical field, showing satisfactory effects, especially in the management of chronic disease. The aim of this study was to assess the effects of VR cognitive training for individuals with mild cognitive impairment (MCI). Methods: Peer-reviewed articles were searched from the PubMed, Embase, Web of Science, the Cochrane Library, Science Direct, and EBSCOhost database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
33
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 44 publications
6
33
2
Order By: Relevance
“…Exercises in semi-immersive VR representing a virtual supermarket mixed with physical activity (such as using a treadmill) has been proposed as an alternative that could ultimately translate to improvements in daily life activities (32). Evidence using a VR cognitive training system in patients with mild cognitive impairment (MCI), a prodromal state to AD, shows moderate effects in global cognitive functioning (33). Stroke rehabilitation using an ecological valid simulating ADLs scenario can have a positive impact in post-stroke individuals, showing larger improvements than conventional methods (34).…”
Section: Cognitive Training and Rehabilitation In Vrmentioning
confidence: 99%
“…Exercises in semi-immersive VR representing a virtual supermarket mixed with physical activity (such as using a treadmill) has been proposed as an alternative that could ultimately translate to improvements in daily life activities (32). Evidence using a VR cognitive training system in patients with mild cognitive impairment (MCI), a prodromal state to AD, shows moderate effects in global cognitive functioning (33). Stroke rehabilitation using an ecological valid simulating ADLs scenario can have a positive impact in post-stroke individuals, showing larger improvements than conventional methods (34).…”
Section: Cognitive Training and Rehabilitation In Vrmentioning
confidence: 99%
“…A number of recent research e orts have provided invaluable insights on understanding and applying virtual reality from a multidisciplinary point of view. In recent years, virtual reality-based education is being expanded in various areas such as medical education, special education, and K-12 or higher education [8,[15][16][17][18]. ere are four major bene ts of virtual reality-based education as follows.…”
Section: Introductionmentioning
confidence: 99%
“…ese studies reviewed the previous articles to answer specific research questions for understanding important keywords or topics of the field. Some review papers focused on the trends of virtual reality-based education research related to specific fields as shown in Table 1, such as Earth science engineering education [7], medical education [8,19], STEM education [20], math education [21], computer science education [22], higher education [23][24][25], heritage education [26], rehabilitation management of breast cancer survivors [27], virtual reality-based training for daily living in patients with chronic stroke [28], PSTD treatments [29], foreign language learning gamification using virtual reality [30,31], K-12 and higher education [15,17], surgical training [32], industrial skills training [31], virtual reality cognitive training in individuals with mild cognitive impairment [16,18], science education [33,34], sensorimotor learning [35], dental education [36], virtual reality-based emotional response and symptom provocation in patients with OCD (obsessive compulsive disorder) [37], nursing education [38,39], virtual reality therapy for social anxiety disorder [40], evacuation training [41], virtual reality-assisted neuromuscular therapy [42], home-based virtual reality rehabilitation for individuals with Parkinson disease [43], virtual realitybased physiology and anatomy learning [44], social work education [45], and marketing higher education …”
Section: Introductionmentioning
confidence: 99%
“…However, such knowledge can cause cognitive overload, which might negatively impact the participants' performance [19]. Zhong studied that VR training may help individuals with their cognitive and executive function [20]. Another study stated that CL will play a major part in high IVR device applications in the future and many researchers want to explore CL in these new environments [21].…”
Section: Introductionmentioning
confidence: 99%